Assessing the Knowledge, Attitude and Practice of Menstrual Hygiene Management Among Junior High Schools Adolescent Females in the Yendi Municipality in the Northern Region of Ghana - Boakye-Yiadom, Akwasi; Aladago, David Alatule; Beweleyir, Julien; Mohammed, Hamza Bawa; Salifu, Marian Fairuza; Asaarik, Mathias (European Scientific Journal, ESJ, 2018)
Introduction: Every year, different batches of adolescent girls between the ages of 10-19 years experience menarche often unprepared to manage the menstruation hygienically. In Ghana, most girls enter adolescence when they are in basic schools, which make menstrual hygiene among girls in Junior High Schools very important. This study examined the knowledge, attitudes, and practices of menstrual hygiene management among both premenarcheal and post-menarcheal adolescent students in basic schoolsin the Yendi Municipality in Ghana. Methods: the study was cross sectional and used quantitative research methods. Semi-structured questionnaires were used to collect data from the female adolescent students aged 10-19 years. A total of 412 female adolescents from 9 basic schools in the Yendi Municipality participated in the study. Students were scored for their level of knowledge, attitude and practices of menstrual hygiene management. Results: The study found that although awareness of menstruation was universal, the Likert scores showed that 67.5% had adequate knowledge of menstrual hygiene management. About a tenth (13.6%) of the adolescent female students had a positive attitude towards menstrual hygiene management and a third (31.1%) practised good menstrual hygiene management. Older age and living with both parents were the main predictors of knowledge of menstrual hygiene management (P < 0.05). Similarly, age, staying with both parents, staying with mother only, access to funds and having adequate knowledge of menstruation were the main determinants of good menstrual hygiene management practice among adolescent girls in basic schools in Yendi Municipality (P < 0.05). Conclusions and recommendations: more than half of the respondents have adequate knowledge but their awareness and knowledge did not translate to positive attitude towards good menstrual hygiene management practices due to negative socio-cultural norms and practices among others that tend to stigmatise menstruation.